PENINGKATAN MINAT BELAJAR BAHASA INDONESIA DENGAN MENGGUNAKAN METODE DEMONSTRASI PADA SISWA KELAS V UPT SPF SD INPRES KAMPUS IKIP KOTA MAKASSAR: Penelitian Tindakan Kelas - Ulfa Ramdhana; Sulhijja Bahrum; Nurul Magfirah (STKIP Subang, 2024)
This study aims to describe the increase in interest in learning Indonesian using the demonstration method in class V students of UPT SPF SD Inpres Kampus IKIP. The demonstration method is a way of presenting teaching materials or lessons by showing or demonstrating to students a certain situation, process, or object being studied, either imitation or real, which is also accompanied by a lecture method or in other words oral explanation so that it can strengthen and improve student learning outcomes in the material. This study uses the Classroom Action Research (CAR) type with data collection techniques through questionnaires and observations. The instruments in this study were questionnaires and observation sheets for the implementation of learning. The results of the study showed that there was an increase in interest in learning Indonesian using the demonstration method in class V students of UPT SPF SD Inpres Kampus IKIP. The increase in student learning interest was marked by an increase in value from cycle I to cycle II. This can be seen in cycle I as many as 60% of students who have a sufficient learning interest category because they are in the range of 52-67, then in cycle II it increased to 100% of students who have a very high learning interest category because they are in the range of 84-100.